Fourteen‐day high‐dose esomeprazole, amoxicillin and metronidazole as third‐line treatment for Helicobacter pylori infection. Issue 9 (4th September 2017) - Puig, Ignasi; González‐Santiago, Jesús M.; Molina‐Infante, Javier; Barrio, Jesús; Herranz, Maria Teresa; Algaba, Alicia; Castro, Manuel; Gisbert, Javier P.; Calvet, Xavier
Summary: Introduction: The efficacy of currently recommended third‐line therapies for Helicobacter pylori is suboptimal, even that of culture‐guided treatments. Resistance to multiple antibiotics is the major factor related to treatment failure. The aim of this study was to evaluate the effectiveness and safety of a 14‐day therapy using high‐dose of amoxicillin, metronidazole and esomeprazole. Material and methods: Multicenter open‐label study as a register in routine clinical practice in patients with two previous failures of eradication therapy. A triple therapy with esomeprazole 40 mg b.d., amoxicillin 1 g t.d.s and metronidazole 500 mg t.d.s for 2 weeks was administered as a third‐line therapy after a first treatment including clarithromycin and a second treatment including a quinolone. Helicobacter pylori status was determined by either histology or 13 C‐UBT both before and after treatment. Results: A total of 68 patients were included in this study. An interim analysis showed that only three out of eight patients who had received metronidazole in previous eradication regimens were cured (37%, 95% CI 8‐75); as a result, after this interim analysis only metronidazole‐naïve patients were included. The ITT eradication rate in metronidazole‐naive patients was 64% (95% CI 51‐76). Adverse events occurred in 58% of patients, all of them mild‐to‐moderate. Two patients (3%) did not complete >90% of the treatment because of side effects. No severe adverse events occurred. Conclusion: Cure rates of this 14‐day schedule using high‐dose esomeprazole, amoxicillin and metronidazole as a third‐line eradication regimen were suboptimal, especially in patients who had received metronidazole in previous failed eradication regimens.